Clinical and Virologic Characteristics and Outcomes of Coronavirus Disease 2019 at a Cancer Center. (16th April 2021) - Yoke, Leah H; Lee, Juhye M; Krantz, Elizabeth M; Morris, Jessica; Marquis, Sara; Bhattacharyya, Pooja; So, Lisa; Riedo, Francis X; Simmons, Jason; Khaki, Ali Raza; Cheng, Guang-Shing; Greninger, Alexander L; et al.
Abstract: Background: High morbidity and mortality have been observed in patients with cancer and coronavirus disease 2019 (COVID-19); however, there are limited data on antimicrobial use, coinfections, and viral shedding. Methods: We conducted a retrospective cohort study of adult patients at the Seattle Cancer Care Alliance diagnosed with COVID-19 between February 28, 2020 and June 15, 2020 to characterize antimicrobial use, coinfections, viral shedding, and outcomes within 30 days after diagnosis. Cycle threshold values were used as a proxy for viral load. We determined viral clearance, defined as 2 consecutive negative results using severe acute respiratory syndrome coronavirus 2 reverse-transcription polymerase chain reaction results through July 30, 2020. Results: Seventy-one patients were included with a median age of 61 years; 59% had a solid tumor. Only 3 patients had documented respiratory bacterial coinfection. Empiric antibiotics for pneumonia were prescribed more frequently early in the study period (February 29–March 28, 2020; 12/34) compared to the later period (March 29–June 15, 2020; 2/36) ( P = .002). The median number of days from symptom onset to viral clearance was 37 days with viral load rapidly declining in the first 7–10 days after symptom onset. Within 30 days of diagnosis, 29 (41%) patients were hospitalized and 12 (17%) died. Each additional comorbidity was associated with 45% lower odds of days alive and out of hospital in the month following diagnosis in adjusted models. Conclusions: Patients at a cancer center, particularly those with multiple comorbidities, are at increased risk of poor outcomes from COVID-19. Prolonged viral shedding is frequently observed among cancer patients, and its implications on transmission and treatment strategies warrant further study. Abstract : A retrospective study of adult patients with COVID-19 at a cancer center demonstrates increased risk of poor outcomes among those with multiple comorbidities. Viral loads declined rapidly within 7–10 days after symptom onset, but prolonged shedding was observed.